Assessing the impact of future climate scenarios on crop water requirements and agricultural water supply across different climatic zones of Pakistan - Shafeeque, Muhammad; Bibi, Amna (Frontiers in Earth Science, 2023)
This study investigates the potential impacts of future climate change on crop water requirements (CWR) in different climatic zones of Pakistan and the subsequent implications for agricultural water demand and supply. Using the latest CMIP6 climate projections, we focused on Rabi and Kharif crop seasons, which are crucial for the growth of major crops in Pakistan. An empirical climate-crop and a hydrological model based on the Budyko theory were modified and forced to project future CWR changes and the potential widening of the water demand-supply gap until 2100. Our results indicate a significant rise in mean annual CWR across all zones and emissions scenarios, with increasing rates at 2.30-2.57 mm/yr under SSP585 and 1.0-1.26 mm/yr under SSP245. Both Rabi and Kharif seasons show rising CWR, notably more under SSP585 (Kharif: 8-14%, Rabi: 12-15%) than SSP245 (Kharif: 4-7%, Rabi: 6-8%). The demand-supply gap is expected to grow notably, with arid and semi-arid zones being the most affected. Compared to 2015-2025, by 2091-2100, the gap increased by 7-15% (SSP245) and 15-28% (SSP585) for Kharif and 7-13% (SSP245) and 13-32% (SSP585) for Rabi. To address these challenges, we recommend strategies like enhancing irrigation efficiency, adjusting crop patterns, and developing heat-resilient crops. Our insights aim to inform policy decisions on agriculture and water management in Pakistan under future climate change.